Pengaruh Sikap Dan Cara Belajar terhadap Prestasi Belajar Sejarah di SMA Negeri Kecamatan Cibinong Bogor - Warhamni, Siti (Jurnal Gemaedu, 2019)
The purpose of this study is to Influence Attitudes and Ways of Learning Together Against the Learning Achievement of History of State High Schools in Cibinong Sub district, Bogor Regency. The research method is a survey with correlation and regression analysis techniques to determine the effect of each variable. The sample used as the object of research is collected students and then analyzed the descriptive statistics and test requirements for data analysis before testing the hypothesis. While secondary data obtained from school documentation is the value of Middle Semester Test (UTS). From the results of data analysis and hypothesis testing, conclusions are obtained that: (1) There is a significant effect of attitudes and ways of learning together on the historical learning achievement of high school students in Cibinong District, Bogor Regency. (2) Against a significant influence on attitudes towards learning achievement History of the National High School students in Cibinong District, Bogor Regency. (3) There is a significant effect of learning methods on the learning achievement of History of State High School students in Cibinong District, Bogor Regency.